Analisis Rasio Profitabilitas sebagai Alat Ukur Kinerja Keuangan PT Cakra Buana Resources Energi TBK - Muh Jusman; Hairul Hairul; Nur Hikmah Handayani; Eko Edy Susanto (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
PT Cakra Buana Resources Energi Tbk is a maritime transportation services company listed on the Indonesia Stock Exchange since January 2023. In a highly competitive capital market and volatile energy sector, evaluating financial performance through profitability ratios is essential for management, investors, and creditors. This study aims to analyze the financial performance of the company during the 2022–2025 period using four profitability indicators: Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). A descriptive quantitative approach is applied using secondary data from audited financial statements obtained from the Indonesia Stock Exchange. The analysis involves ratio calculation, comparison with industry standards, and trend analysis over time. The results show that all profitability ratios consistently remain below industry benchmarks, with average values of GPM at 23.26% (standard: 30%), NPM at –46.44% (standard: 20%), ROA at –3.24% (standard: 30%), and ROE at –46.41% (standard: 40%). The declining trend is mainly driven by rising cost of revenue reaching 97.3% in 2025, increasing administrative expenses after the IPO, and higher financial costs due to debt-financed expansion, including the acquisition of the Hai Long 106 vessel worth USD 100 million. The independent auditor also issued a going concern warning in 2025. The study suggests cost efficiency and revenue optimization strategies to improve profitability.